2017
DOI: 10.1021/acs.macromol.6b02811
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of an Exact Polystyrene-graft-polyisoprene: A Failure of Size Exclusion Chromatography Analysis

Abstract: An exact polystyrene-graf t-polyisoprene (PS-g-PI) synthesized by iterative anionic polymerization and graft reaction using diphenylethylene functional groups was characterized by liquid chromatography. As-prepared graft copolymer contains various byproducts other than the target PS-g-PI. After the fractionation by size exclusion chromatography (SEC), the PS-g-PI appears quite homogeneous by SEC analysis, but the temperature gradient interaction chromatography (TGIC) separation with respect to the PI branch nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…This can be explained by the fact that SEC is a relative method and hydrodynamic radii for the amphiphilic P2VP‐grafted PS‐ b ‐PI strongly differ compared to PS homopolymers which were used as SEC standards. A remarkable failure of SEC for grafted PI chains with PS was recently described by the Hirao group . Therefore, values obtained from the NMR spectra for the purified samples are closer to the absolute values for molar masses compared to results obtained by SEC.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…This can be explained by the fact that SEC is a relative method and hydrodynamic radii for the amphiphilic P2VP‐grafted PS‐ b ‐PI strongly differ compared to PS homopolymers which were used as SEC standards. A remarkable failure of SEC for grafted PI chains with PS was recently described by the Hirao group . Therefore, values obtained from the NMR spectra for the purified samples are closer to the absolute values for molar masses compared to results obtained by SEC.…”
Section: Resultssupporting
confidence: 64%
“…Polybutadiene (PBd) segments were grafted with polystyrene (PS) by anionic polymerization after hydrosilylation of the PBd backbone with pendant chlorosilane moieties . Very recently, the Hirao group reported on the preparation and analysis of precisely grafted polystyrene‐ block ‐polyisoprenes, via iterative anionic polymerization and a graft reaction using diphenylethylene (DPE) functional groups …”
Section: Introductionmentioning
confidence: 99%
“…Advances in high‐temperature gradient interaction chromatography (TGIC) will help polymer chemists gain deeper insight into the block copolymers with complicated architectures. For example, a recent TGIC study, accompanied by liquid chromatography at critical condition (LCCC) analysis, revealed that the multigraft copolymers synthesized by the iterative method are actually highly heterogeneous in graft copolymer architecture, rather than homogenous as indicated by conventional size exclusive chromatography (SEC) analysis . Getting a more realistic assessment of the true structure of graft copolymer products will in return allow chemists.…”
Section: Resultsmentioning
confidence: 99%
“…In general, size‐exclusion chromatography (SEC) is the most widely used tool to characterize polymers and provides the molar mass and molar mass distribution with respect to the hydrodynamic volume of the polymers usually using linear polystyrenes with narrow molar mass distributions as calibration standards . However, it is difficult to obtain accurate analysis of complex polymers with different topologies using SEC alone because polymers with the same hydrodynamic volume but different topologies may coelute . No doubt, it is necessary to combine SEC with other methods, such as normal‐phase temperature gradient interaction chromatography (NP‐TGIC), reversed‐phase temperature gradient interaction chromatography (RP‐TGIC), solvent gradient interaction chromatography (SGIC), and liquid chromatography at critical condition (LCCC) to form a two‐dimensional detection system to characterize complex polymers.…”
Section: Introductionmentioning
confidence: 99%